2018
DOI: 10.1159/000493499
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysone Elicits Chronic Renal Impairment via Mineralocorticoid-Like Pathogenic Activities

Abstract: Background/Aims: Ecdysteroids are steroidal insect molting hormones that also exist in herbs. Ecdysteroid-containing adaptogens have been popularly used to improve well-being and by bodybuilders for muscle growth. However, the use of ecdysone in mammals is also associated with kidney growth and enlargement, indications of disturbed kidney homeostasis. The underlying pathogenic mechanism remains to be clarified. Methods: Virtual screening tools were employed to identify compounds that are homologous to ecdysone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Recently (Lu et al 2018a, b), it has been suggested that ecdysone (E, which is rarely a major phytoecdysteroid) has detrimental effects on renal function in mice at a dose of 6 μg/g/d, bringing about glomerular injury and proteinuria. The authors propose that E acts as a mimic of aldosterone, activating the mineralocorticoid nuclear receptor (MR), and that the detrimental effects can largely be blocked by spironolactone, an antagonist of MR. As yet, it is not known if these effects are common to other ecdysteroids, e.g., 20E.…”
Section: Ecdysone and Effects On The Kidneymentioning
confidence: 99%
“…Recently (Lu et al 2018a, b), it has been suggested that ecdysone (E, which is rarely a major phytoecdysteroid) has detrimental effects on renal function in mice at a dose of 6 μg/g/d, bringing about glomerular injury and proteinuria. The authors propose that E acts as a mimic of aldosterone, activating the mineralocorticoid nuclear receptor (MR), and that the detrimental effects can largely be blocked by spironolactone, an antagonist of MR. As yet, it is not known if these effects are common to other ecdysteroids, e.g., 20E.…”
Section: Ecdysone and Effects On The Kidneymentioning
confidence: 99%
“…Additionally, aldosterone plays a key role in the pathophysiology of hypertension, chronic heart failure [9], myocar-dial infarction remodeling [6][7][8]. The mineralocorticoid receptor (MR) activated by aldosterone can increase the synthesis of collagen [10], induce inflammation [11,12], modulate oxidative stress [13][14][15], promote cell migration [16], and induce apoptosis [17,18]. Aldosterone can also increase calcification in vascular smooth muscle cells [19,20].…”
Section: Introductionmentioning
confidence: 99%